2014
DOI: 10.7314/apjcp.2014.15.11.4651
|View full text |Cite
|
Sign up to set email alerts
|

Gelam Honey and Ginger Potentiate the Anti Cancer Effect of 5-FU against HCT 116 Colorectal Cancer Cells

Abstract: The development of chemopreventive approaches using a concoction of phytochemicals is potentially viable for combating many types of cancer including colon carcinogenesis. This study evaluated the anti-proliferative effects of ginger and Gelam honey and its efficacy in enhancing the anti-cancer effects

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 55 publications
1
48
0
1
Order By: Relevance
“…Another research done by a researcher called Hakim T. also supports what Tahir did conclude in his research but he found that GH enhances anti-cancer effect of 5-FU (5-flurouracill) against colorectal cancers (13,14).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Another research done by a researcher called Hakim T. also supports what Tahir did conclude in his research but he found that GH enhances anti-cancer effect of 5-FU (5-flurouracill) against colorectal cancers (13,14).…”
Section: Introductionsupporting
confidence: 52%
“…Tahir T. and his colleagues examined the GH on colon cancer cells and they conclude that it may be an effective chemo-preventive and therapeutic strategy for inducing death to colon cancer cells (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies (Unal et al, 2013;Hakim et al, 2014) have discussed the combinational effect of 5-FU with other agents, they found that the combination chemotherapy of Gemcitabine, Folinic Acid and 5-FU has a more obvious anti-cancer effect but as well as toxicity. So the combination of a natural, low-toxicity and highefficacy agents with 5-FU may be better.…”
Section: Suppressive Effect Of Sinomenine Combined With 5-fluorouracimentioning
confidence: 99%
“…Combination treatment of GH and ginger extract showed synergistic effects via increasing the apoptotic rate of HCT 116 colon cancer cells and reducing the 1C 50 of GH required for inhibiting the cells growth. It also showed that cotreatment of GH with Flurouracil (5-FU) has potential anti-tumour effect against colorectal cancer cell by reducing the cell growth compared to the treatment with 5-FU alone (Hakim et al 2014).…”
Section: Anticancer Properties Of Ghmentioning
confidence: 99%